Reducing Rural Household Poverty in Ghana: A Case Study of Women in Non-Farm Enterprise Activity in Kassena-Nankana District (Journal of Science and Technology, 2016)
Through no conscientious strategic policy orientation, rural women in the Kassena-Nankani District are waling a perceptible impact on household poverty reduction in their domain. They do it through their engagement in non-farm economic activities. On the basis of a number, the results of this research show that non-farm small enterprises activities constitute major sources of employment and income generation to rural women from which they make a contribution to household expenditure. The rural women entrepreneur, are able to support the provision of basic household needy and the development of sustainable household livelihood systems. Through that, industrious women are able to gain social recognition and respect at the household and community level., To improve the situation and optimize the contribution of rural women to household pas ern reduction, the study recommends the promotion of non-farm based employment for rural women.